Komparasi Metode Weighted Product (WP) Dan Simple Additive Weighting (SAW) Pada Sistem Pendukung Keputusan Dalam Menentukan Pembangunan Infrastruktur Desa - Yandi Makmur; Agung Triayudi; Arie Gunawan (Journal of Computer System and Informatics (JoSYC), 2023)
Government initiatives to give villages more power include village development. In accordance with local village government policies, there are specific criteria for allocating village infrastructure development funds. The goal is for village infrastructure development to be more equitable and directed. Priorities for developing village infrastructure must be decided. Decisions on village infrastructure development are still made by voting, and often more significant developments have to be postponed due to a vote loss. To determine priorities for village infrastructure development, village officials can use a decision support system (Decision Support System). Village infrastructure development priorities are determined using the Simple Additive Weight (SAW) and Product Weight (WP) methodologies. Each proposal will be assessed according to the criteria selected by the village to set development priorities. It is hoped that by creating a decision support system it will be easier, more accurate and faster to determine development priorities in the village of Rawa Panjang when using the SAW and WP methodologies to prioritize village infrastructure development. Results Based on the research, it is recommended to use the WP method to determine the ranking, because the level of suitability of data in the field is higher than SAW which was found to be 99.87 WP and SAW was determined to be 99.27%